Ways to the West : How Getting Out of Our Cars Is Reclaiming America's Frontier - Sullivan, Tim, 1978- (Book collections on Project MUSE., 2015)
"Sullivan uses his careless road trip through the intermountain West to explore how the region is taking on what may be its largest challenge: sustainable transportation. Combining personal travel narrative, historical research, and professional expertise in urban planning, Sullivan takes a critical look at how contemporary Western cities are making themselves more hospitable to life less centered automotive transportation"--Provided by publisher.